The Marcus Garvey and Universal Negro Improvement Association Papers. - Hill, Robert A., 1943-; Garvey, Marcus, 1887-1940; Forczek, Deborah; Tolbert, Emory J. (University of California Press, 1983)
This second volume of Robert A. Hill's monumental ten-volume survey of Marcus Mosiah Garvey's extraordinary mass movement of black social protest covers a period of rapid growth. The Universal Negro Improvement Association, with its ""Africa for the Africans"" program of racial nationalism, rapidly gained in strength in the aftermath of Garvey's successful meeting in Carnegie Hall in August 1919, and culminated in its spectacular First International Convention.